Intrinsic-signal optical imaging reveals cryptic ocular dominance columns in primary visual cortex of new world owl monkeys - Kaskan, Peter M.; Lu, Haidong D.; Dillenburger, Barbara C.; Roe, Anna W.; Kaas, Jon H. (Frontiers in Neuroscience, 2007)
A significant concept in neuroscience is that sensory areas of the neocortex have evolved the remarkable ability to represent a number of stimulus features within the confines of a global map of the sensory periphery. Modularity, the term often used to describe the inhomogeneous nature of the neocortex, is without a doubt an important organizational principle of early sensory areas, such as the primary visual cortex (V1). Ocular dominance columns, one type of module in V1, are found in many primate species as well as in carnivores. Yet, their variable presence in some New World monkey species and complete absence in other species has been enigmatic. Here, we demonstrate that optical imaging reveals the presence of ocular dominance columns in the superficial layers of V1 of owl monkeys (Aotus trivirgatus), even though the geniculate inputs related to each eye are highly overlapping in layer 4. The ocular dominance columns in owl monkeys revealed by optical imaging are circular in appearance. The distance between left eye centers and right eye centers is approximately 650 µm. We find no relationship between ocular dominance centers and other modular organizational features such as orientation pinwheels or the centers of the cytochrome oxidase blobs. These results are significant because they suggest that functional columns may exist in the absence of obvious differences in the distributions of activating inputs and ocular dominance columns may be more widely distributed across mammalian taxa than commonly suggested.